The Effectiveness of Problem Based Learning Model in Improving Students' Higher Order Thinking Skills - Fitria Puteri Arviani; Dinn Wahyudin; Laksmi Dewi (Jurnal Pendidikan Indonesia, 2023)
This research was motivated by the low ability of students to understand scientific concepts and solve scientific problems. The aim of this research is to analyze the effectiveness of the PBL learning model in improving Higher Order Thinking Skills (HOTS) abilities. A quantitative approach was used in this research using the Quasi Experimental method with a Non Equivalent Control Group design to determine the effectiveness of learning using the problem based learning (PBL) model in improving students' high-level thinking skills in vocational school student product competencies. The sample selection technique used was purposive sampling by selecting a sample of 200 class III vocational school students. Data is collected by using is pretest-intervention-posttest. The test conducted in normality, homogeneity, and hypothesis tests. The results of the research show that the problem-based learning method is effective in improving high-level thinking abilities significantly compared to control abilities using conventional methods. Overall student cognitive learning outcomes from the pre-test and post-test always increase, where in the experimental class it increases from 28.45 to 68.6 while in the control class it increases from 23.78 to 55.32. Then a Wilcoxon test of 0.000 (2-tailed sig <0.05) was carried out to determine the magnitude of the intervention effect. Based on the test results, students who received intervention with PBL experienced a significant increase in high-level thinking skills in product competency for vocational school students compared to students who received intervention with conventional methods.